Development, feasibility, and acceptability of a smartphone-based ecological momentary assessment of minority stress and suicidal ideation among sexual and gender minority youth - Kirsty Clark; Kaitlyn Phillips; Elisa Park; Alexandra Argiros; Alexandros Nikolaidis-Konstas; Joseph Sexton; Melissa Cyperski; Evan Kleiman; John Pachankis (PLoS ONE, 2025)
Objective We sought to develop and assess the feasibility and acceptability of a smartphone-based ecological momentary assessment (EMA) study of minority stress and suicidal ideation intensity among sexual and gender minority youth (SGMY) in the US Southeast. Methods In Study 1, the EMA protocol was developed through an iterative process, incorporating qualitative input from focus groups and interviews with 16 parents of SGMY and 16 SGMY from the US Southeast as well as six clinicians and researchers. In Study 2, 50 SGMY aged 13–24 with past-year suicidal ideation and current depressive symptoms were recruited from the US Southeast. The study included a baseline assessment, 28 consecutive days of EMA surveys (3x per day), a weekly acceptability survey, and a post-study exit interview. Results In Study 1, qualitative feedback guided the selection, adaptation, and development of EMA measures and informed study features including the EMA schedule, reminder notifications, incentive structure, and the safety and risk monitoring protocol. In Study 2, the EMA protocol demonstrated feasibility through high compliance with the EMA survey (M = 80.21%, SD = 16.92%, Mdn = 83.93%, range = 38.10%−100.00%) with some variation over time and by participant age. Weekly feedback surveys indicated high acceptability, with participants reporting that the EMA surveys were easy to complete and private, understandable, minimally burdensome, and at least moderately engaging. Exit interviews revealed several themes, including facilitators of high engagement, barriers to engagement, intervention implications, and suggested improvements for future EMA studies. Conclusions Smartphone-based EMA is a feasible and acceptable method for studying real-time experiences of minority stress and suicidal ideation intensity among SGMY at high risk. Incorporating community member feedback during EMA study development can help to ensure cultural responsiveness and enhance participant compliance. This paper provides practical guidance for researchers planning to conduct EMA suicide research with SGMY.